College Students’ Academic Procrastination during the Covid-19 Pandemic: Focusing on Academic Achievement - Basith, Abd; Rahman, Md Shahinoor; Moseki, Usina Robert (Jurnal Kajian Bimbingan dan Konseling, 2021)
This research aims to describe the level of college students’ academic procrastination, analyze differences in academic procrastination among the college students, and analyze the relationship between academic procrastination and academic achievement. This research uses a quantitative method with a survey and correlational design. The research population is 620 Sekolah Tinggi Keguruan dan Ilmu Pendidikan Singkawang (STKIP) Singkawang college students. The sample is taken using a simple random sampling technique as many as 352 college students (76 male and 276 female). The instrument used in data collection is the academic procrastination scale and great point academic. The data are analyzed using descriptive analysis, ANOVA, and correlation. The findings show that college students’ academic procrastination is at a moderate level which is dominated by time management skill indicators. Male students and students who are in the middle years have higher levels of academic procrastination. Intercorrelation shows a significant but negative relationship between academic procrastination and academic achievement.